Serum protein changes in a rat model of chronic pain show a correlation between animal and humans - Bellei, Elisa (Sci Rep, 2017)
In previous works we showed the overexpression of some proteins in biological fluids from patients suffering chronic pain. In this proteomic study we analysed serum from a rat model of neuropathic pain obtained by the chronic constriction injury (CCI) of sciatic nerve, at two time intervals, 2 and 5 weeks after the insult, to find proteins involved in the expression or mediation of pain. Sham-operated and CCI rats were treated with saline or indomethacin. Two weeks after ligation, we identified three serum proteins overexpressed in CCI rats, two of which, alpha-1-macroglobulin and vitamin D-binding protein (VDBP), remained increased 5 weeks post-surgery; at this time interval, we found increased levels of further proteins, namely apolipoprotein A-I (APOA1), apolipoprotein E (APOE), prostaglandin-H2 D-isomerase (PTGDS) and transthyretin (TTR), that overlap the overexpressed proteins found in humans. Indomethacin treatment reversed the effects of ligation. The qPCR analysis showed that transcript levels of APOA1, APOE, PTGDS and VDBP were overexpressed in the lumbar spinal cord (origin of sciatic nerve), but not in the striatum (an unrelated brain region), of CCI rats treated with saline 5 weeks after surgery, demonstrating that the lumbar spinal cord is a possible source of these proteins.